Examining the effect of workplace friendships and job embeddedness on turnover intention (the case of mashhad as a tourist destination in Iran) - Asgharian, Reza (2013)
In our contemporary times, most corporate organizations have put more importance on the role of human resource in underscoring the success of the organization. They have come to appreciate the significance of human resources to having potential impact of the organization?s performance and its vital factor used as a vehicle towards potential success in the midst of competition. This study review theory and research on workplace friendships, job embeddedness, and then combines them into a model of turnover intention for hospitality industry in (Mashhad) Iran. The qualitative method design used for this study to provide a comprehensive understanding of the research problem. The study used the qualitative method approach that consists of semi-structured interviews. Each participant answered the research questions that assesses his/her perception towards friendships. According to the qualitative method, a portion of the participants were randomly selected to complete the interview process where more information is collected.